A Comparison of Clinical Outcomes of Dislocated Intraocular Lens Fixation between In Situ Refixation and Conventional Exchange Technique Combined with Vitrectomy - Sun Jung Eum; Myung Jun Kim; Hong Kyun Kim (Journal of Ophthalmology)
Purpose. To evaluate surgical efficacy of in situ refixation technique for dislocated posterior chamber intraocular lens (PCIOL). Methods. This was a single-center retrospective case series. 34 patients (34 eyes) who underwent sclera fixation for dislocated IOLs combined with vitrectomy were studied. Of 34 eyes, 17 eyes underwent IOL exchange and the other 17 eyes underwent in situ refixation. Results. Mean follow-up period was 6 months. Mean logMAR best corrected visual acuity (BCVA) was not significantly different between the groups 6 months after surgery (0.10±0.03 in the IOL exchange group and 0.10±0.05 in the refixation group; p=0.065). Surgically induced astigmatism (SIA) was significantly lower in the refixation group (0.79±0.41) than in the IOL exchange group (1.29±0.46) (p=0.004) at 3 months, which persisted to 6 months (1.13±0.18 in the IOL exchange group and 0.74±0.11 in the refixation group; p=0.006). Postoperative complications occurred in 3 eyes in the IOL exchange group (17.6%) and 2 eyes in the refixation group (11.8%). However, all of the patients were well managed without additional surgery. Conclusion. The in situ refixation technique should be preferentially considered if surgery is indicated since it seemed to produce a sustained less SIA compared to IOL exchange.